Alcohol Consumption, Alcohol Outlets, and the Risk of Being Assaulted With a Gun - Branas, Charles C. (Alcoholism, 2009)
Peer Reviewedhttp://deepblue.lib.umich.edu/bitstream/2027.42/65835/1/j.1530-0277.2009.00912.x.pd